Influence of Delayed Conductance on Neuronal Synchronization - Protachevicz, Paulo R.; Borges, Fernando S.; Iarosz, Kelly C.; Baptista, Murilo S.; Lameu, Ewandson L.; Hansen, Matheus; Caldas, Iberê L.; Szezech, José D.; Batista, Antonio M.; Kurths, Jürgen (Frontiers in Physiology, 2020)
In the brain, the excitation-inhibition balance prevents abnormal synchronous behaviour. However, known synaptic conductance intensity can be insufficient to account for the undesired synchronisation. Due to this fact, we consider time delay in excitatory and inhibitory conductances and study its effect on the neuronal synchronisation. In this work, we build a neuronal network composed of adaptive integrate-and-fire neurons coupled by means of delayed conductances. We observe that the time delay in the excitatory and inhibitory conductivities can alter both the state of the collective behaviour (synchronous or desynchronous) and its type (spike or burst). For the weak coupling regime, we find that synchronisation appears associated with neurons behaving with extremes highest and lowest mean firing frequency, in contrast to when desynchronisation is present when neurons do not exhibit extreme values for the firing frequency. Synchronization can also be characterised by neurons presenting either the highest or the lowest levels in the mean synaptic current. For the strong coupling, synchronous burst activities can occur for delays in the inhibitory conductivity. For approximately equal-length delays in the excitatory and inhibitory conductances, desynchronous spikes activities are identified for both weak and strong coupling regimes. Therefore, our results show that not only the conductance intensity but also short delays in the inhibitory conductance are relevant to avoid abnormal neuronal synchronisation.